Impact of Nation Branding Campaigns on Country Image: Germany vs. Brazil - Anca-Georgiana Andrei (Cactus, 2016)
The purpose of this paper is to show how a successful nation brand campaign can influence the image of a country and to highlight its positive impact on different areas such as tourism or foreign investments. Two nation branding campaigns, implemented one in Germany and one in Brazil, during FIFA World Cup, 2006 and 2014, were examined in comparison in order to write out the necessary conclusions which support the hypothesis above. The study also proposes to demonstrate that Blue Ocean Strategy was used with success in Germany’s nation branding campaign.